PENINGKATAN KETERAMPILAN MENULIS CERPEN MELALUI METODE PEMBELAJARAN BERBASIS PENGALAMAN DAN MEDIA AUDIOVISUAL PADA SEKOLAH MENENGAH PERTAMA - Mastini, Mastini; Suwandi, Sarwiji; Sumarwati, Sumarwati (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
The aims of this research is to improve students the quality of learning process and improving skill of writing short stories text skills. The subject of the study was student class VII D and a teacher in SMP Negeri 1 Juwana. The application of Experiential Learning Method and audiovisual media are to improve the quality of learning process and improving skill of writing short stories text and changing behaviors, religious and social attitudes of students to be better. This research shaped Classroom Action Research. Techniques of data collection is done by observation, interviews, tests and document analysis. The research process is performed in two cycles. Every cycle consists of four stages, namely planning, implementation, observation, and reflection. The subject of this research was the class VII D total students is 32 and teachers as collaborators. Data collection technique are observation, interview, test and document analysis. The validity of the data used triangulation techniques and review the informant. Data analysis used comparative analysis techniques and technical descriptions of critic analysis. The result of this research shows Experiential Learning Method and audiovisual media through can be used for improving the learning-process quality in writing short story text and improving skill of writing short story text. The conclusion of this research is implementing Experiential Learning method and audiovisual media can improve the learning-process quality and skill of writing short stories of VII D students in SMP Negeri 1 Juwana.